A Short Review of Membrane Fouling in Forward Osmosis Processes - Youngpil Chun (Membranes, 2017)
Interest in forward osmosis (FO) research has rapidly increased in the last decade due to problems of water and energy scarcity. FO processes have been used in many applications, including wastewater reclamation, desalination, energy production, fertigation, and food and pharmaceutical processing. However, the inherent disadvantages of FO, such as lower permeate water flux compared to pressure driven membrane processes, concentration polarisation (CP), reverse salt diffusion, the energy consumption of draw solution recovery and issues of membrane fouling have restricted its industrial applications. This paper focuses on the fouling phenomena of FO processes in different areas, including organic, inorganic and biological categories, for better understanding of this long-standing issue in membrane processes. Furthermore, membrane fouling monitoring and mitigation strategies are reviewed.